Pengaruh Penggunaan BYond by BSI terhadap Kepuasan Nasabah di Kabupaten Sumbawa - Siti Rahmawati; Rozzy Aprirachman (SENTRI: Jurnal Riset Ilmiah, 2026)
This study analyzes the influence of the use of the BYond by BSI application on customer satisfaction in Sumbawa Regency, with features, accessibility, and ease of use as exogenous variables and intensity of use as an intervening variable. The research employs a quantitative associative approach with a sample of 100 customers using BYond by BSI, determined through purposive sampling after the minimum sample size was calculated using the Lemeshow formula. Data were collected via a Likert-scale questionnaire and analyzed using Structural Equation Modeling based on Partial Least Squares (PLS-SEM) with SmartPLS 4. The evaluation of the measurement model indicates that all indicators are valid and reliable. The model explains 68.5% of the variance in intensity of use and 83.0% of the variance in customer satisfaction. Hypothesis testing results reveal that features do not have a significant effect on either intensity of use or customer satisfaction. Conversely, accessibility and ease of use exert a positive and significant influence on both intensity of use and customer satisfaction, while intensity of use has a positive and significant effect on satisfaction. These findings affirm that the success of digital banking services in Sumbawa Regency is more contingent upon stable access, a simplified user experience, and the routine utilization of the application, rather than merely on the completeness of features.